Cervical spondylotic myelopathy: what the neurologist should know - Celmir de Oliveira Vilaça; Marco Orsini; Marco A. Araujo Leite; Marcos R.G. de Freitas; Eduardo Davidovich; Rossano Fiorelli; Stenio Fiorelli; Camila Fiorelli; Acary Bulle Oliveira; Bruno Lima Pessoa (MDPI AG, 2016)
Cervical spondylotic myelopathy is a wellknown cause of disability among older people. A significant amount of these patients is asymptomatic. Once the symptoms start, the worsening may follow a progressive manner. We should suspect of spondylotic myelopathy in any individual over 55 years presenting progressive changes in gait or losing fine motor control of the upper limbs. Despite its frequent prevalence, this condition is still neglected and many times confused with other supratentorial lesions regarding diagnostic. Here we address some of most important aspects of this disease, calling attention to pathophysiology, the natural history, presentation, differential diagnosis, clinical assessment, and treatment.